EFEKTIVITAS MEDIA AUDIOVISUAL DALAM MENINGKATKAN MINAT BELAJAR PPKN PADA SISWA SEKOLAH DASAR - Adela Sabira Ramadhani; Linda Zakiyah; Juhana Sakmal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the effectiveness of using audiovisual media in increasing students' interest in learning in the subject of Pancasila and Education in Elementary Schools. Interest in learning is one of the important factors in the success of the learning process. Audiovisual media is considered capable of creating more interesting, contextual, and interactive learning. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the use of audiovisual media, such as learning videos, animations, and short films with national themes, can increase students' attention, interest, and active participation in Pancasila ecucation learning. This media also helps students understand abstract or normative material more easily. In conclusion, audiovisual media has proven effective in increasing interest in learnin in Elementary Schools if used appropriately and in accordance with student characteristics.